2022
DOI: 10.20473/j.djmkg.v55.i3.p165-173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of herbal medicine in reducing the severity of oral lichen planus: A systematic review and meta-analysis

Abstract: Background: Oral lichen planus (OLP) is a chronic autoimmune mucocutaneous disease of unknown aetiology. The reported use of herbal medicines may promote the healing of OLP lesions. Purpose: We aim to determine the effectiveness of herbal medicine to reduce the clinical and pain severity of OLP. Methods: PubMed, Cochrane Library and Wiley Online Library were reviewed according to the inclusion criteria. Risk of bias was performed for the randomised control trial (RCT) and cohort studies to assess the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Individuals with either severe cutaneous lichen planus or OLP exhibited higher amounts of IL-6 in their saliva (7). Researchers found that the amount of IL-6 identified in the saliva of OLP patients has fallen to a non-detectable level after different types of therapies (8). Platelet-rich plasma was defined as condensed plasma with high concentration of platelet-derived growth factors, such as: transforming growth factor-β, vascular endothelial growth factors (VEGFs), fibroblast growth factor (FGF), Epidermal growth factor (EGF), insulin-like growth factor 1 (IGF-1), and hepatocyte growth factor (HGF) (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with either severe cutaneous lichen planus or OLP exhibited higher amounts of IL-6 in their saliva (7). Researchers found that the amount of IL-6 identified in the saliva of OLP patients has fallen to a non-detectable level after different types of therapies (8). Platelet-rich plasma was defined as condensed plasma with high concentration of platelet-derived growth factors, such as: transforming growth factor-β, vascular endothelial growth factors (VEGFs), fibroblast growth factor (FGF), Epidermal growth factor (EGF), insulin-like growth factor 1 (IGF-1), and hepatocyte growth factor (HGF) (9) .…”
Section: Introductionmentioning
confidence: 99%